Peningkatan Hasil Belajar IPS Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think Pair and Share (TPS) dengan Teknik Gallery Walk - Kurniasari, Elisabet Febrian; Setyaningtyas, Eunice Widyanti (LPPM Undiksha, 2017)
The background of the problem in this research is the lack of class V student learning result Christian Elementary School 04 Salatiga Eben Haezer. This study aims to improve student learning outcomes using learning model Think Pair Share technique Gallery Walk. This type of research is a classroom action research (CAR) conducted in two cycles. Each cycle consists of four stages: action planning, action, observation and reflection. The results of this study showed an increase in the value of student learning outcomes with minimal completeness criteria (KKM) is ≥70. It can be seen from the students' prior to action, of 25 fifth grade students there are only 11 students who achieve the KKM with a percentage of 44%. Then the action on the first cycle to 20 students who achieve the KKM with a percentage of 80%. In the second cycle of learning outcomes is increasing, reaching the KKM 25 students with a percentage of 100%. So it can be concluded that the use of the learning model Think Pair Share with Gallery Walk techniques to improve learning outcomes in social studies.